Relationship Between Personal Hygiene and the Incidence of Diarrhea on Students 104219 SDN Tanjung Anom - Meutia Nanda; Azzahra Ramadhana Nasution; Tania Yusrina; Ismi Larasati Hasibuan; Rizky Nanda Pratama (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Diarrhea is a disease that is often found in developing countries, including Indonesia, and is the main cause of morbidity and mortality in children. One factor that has a big role is personal hygiene behavior. Elementary school age children are a group that is very vulnerable to diarrheal infections. This study aims to identify the relationship between personal hygiene habits and the incidence of diarrhea in students at SDN 104219 Tanjung Anom. This research uses a quantitative descriptive approach to analyze the relationship between personal hygiene and the incidence of diarrhea in students at SDN 104219 Tanjung Anom. The population in this study consisted of 40 students in grades V and VI who were selected using the purposive sampling method to take the pretest and posttest as a measurement tool. The results of this research can be seen from the increase in the average student score from the pretest of 14.825 to 18.35 on the posttest. Apart from that, the correlation test results show a strong and significant relationship between the pretest and posttest results with an r value of 0.706 and p = 0.000. So it can be said that there is a relationship between personal hygiene and the incidence of diarrhea.